The relationship between action inhibition and athletic performance in elite badminton players and non-athletes - KUN-FU LIAO (Journal of Human Sport and Exercise, 2017)
Racket sports are among the most popular sports in the world. They require higher-order cognitive processes to execute complex actions to achieve successful performance on the court. Action inhibition is the ability to suppress ongoing actions; it is crucial to achieving higher levels of sports performance. The aim of the present study was to investigate the effect of expertise on action inhibition in badminton players and non-athletes. Current study recruited forty-two professional badminton players and matched fifteen non-athlete controls to participate in the study. Badminton player was asked to fill out the questionnaire for collect their information of training background. Matched participants then performed the stop signal task for evaluation of their action inhibition ability. We compare the difference in cognitive performance between badminton player and nonathlete controls group. The results showed that badminton players had a greater likelihood than non-athletes of successfully inhibiting their responses during stop trials. Furthermore, a strong positive correlation indicated that badminton players who participated in higher levels of competition had better performance on response inhibition. To concluded, the present study links the relationship between cognitive ability and athletic performance in badminton player. Moreover, the results of the present study on action inhibition in sports expertise may provide information for future sports training and benefits for those who suffer from cognitive difficulties.